2018
DOI: 10.3390/coatings8080265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding UV Absorbers Embedded in Carbonate Calcium Templates Covered with Light Responsive Polymer into a Clear Wood Coating

Abstract: Abstract:The limited durability of clear coatings is a major issue for the coating and wood industry. The addition of organic UV absorbers improves coating resistance by the absorption and the conversion of the UV radiation into harmless heat. Organic UVAs are prone to degradation and can migrate in the binder of coatings. In this study, commercial UVAs and HALS have been entrapped into CaCO 3 templates coated with stimuli responsive polymers. Microspheres were incorporated into a clear acrylic water-based coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…They found that a loading of 4% of microcapsules was enough to imbue the coating with good self-healing capacities without affecting its mechanical properties. Similarly, Queant et al encapsulated organic UV absorbers in calcium carbonate microspheres in order to protect them from degradation [82]. A 2500 h accelerated weathering test showed that wood coated with a transparent waterborne latex would suffer less color changes when the UV absorbers were encapsulated.…”
Section: Additives In Organic Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a loading of 4% of microcapsules was enough to imbue the coating with good self-healing capacities without affecting its mechanical properties. Similarly, Queant et al encapsulated organic UV absorbers in calcium carbonate microspheres in order to protect them from degradation [82]. A 2500 h accelerated weathering test showed that wood coated with a transparent waterborne latex would suffer less color changes when the UV absorbers were encapsulated.…”
Section: Additives In Organic Coatingsmentioning
confidence: 99%
“…When added to a waterborne acrylic resin as powdered oyster shell, it extended the burning time of the substrate from 18.00 min up to 29.67 min [97]. In order to prevent the premature degradation of organic UV absorbers in a clear acrylic coating, Queant et al built CaCO 3 microcapsules to encapsulate and protect the UV absorbers, increasing their efficiency over a prolonged period [82].…”
Section: Economical Aspectsmentioning
confidence: 99%
“…According to relevant studies [15][16][17][18][19][20], the chemical synthesis processes of the two kinds of coatings are shown in Figure 1. As seen in Figure 1a, first, the addition action occurred in the C=C bonds of the AA, ST, and EA in the case of initiator.…”
Section: Chemical Synthesis and Curing Processmentioning
confidence: 99%
“…Recently, coating processes carried out on materials have received more and more attention because of their good protective and beautifying effects for various substrates [15][16][17][18][19]. With the development of greater environmental protection awareness, waterborne coatings play an important…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that the whole coting process can be divided into several steps, wetting of substrate, leveling, infiltrating, and drying into film [12][13][14]. The hydrophilicity and porosity of substrate has great impact on the coating process and coating performance [15][16][17]. The bamboo scrimber is a kind of high strength bamboo product formed by changing the cell structure of bamboo under the dual action of pressure and resin, which led to the densification of material, less the hydrophilic groups, and the parenchyma and fiber filled by adhesive of bamboo.…”
Section: Introductionmentioning
confidence: 99%